Cathetar Related Antimicrobial Resistance Pattern in Intensive Care Unit Patients: A Single Centre Study - Romana Bibi, Rafi Ullah, Muhammad Izhar, Sijad ur Rehman, Kainat Sheikh, Kalsoom Essa Bhattani (Journal of Rawalpindi Medical College, 2021)
Background Urinary catheter is the most common cause of urinary tract infection (UTI) which has been associated with three fold increase risk in mortality. A high level of resistance was noted among the admitted patients for cephalosporin. The primary aim of the study is to known the strain of pathogens; its drugs sensitivity and resistance in intensive care unit (ICU) patients which help the physician in proper management and reduces the mortality and morbidity in urinary catheter related complication. Methods This study was conducted in Intensive care unit patients of Hayatabad medical complex Peshawar Pakistan over a period of 1 year from 1st January to 31st December 2019. Medical charts were reviewed and 100 patients were selected based on inclusion criteria and their urine culture and sensitivity reports were noted to know about the most common pathogens, its drugs sensitivity and resistance in these patients. Clinical and Laboratory Standards Institute (CLSI) used for uropathogen by culture and Disc diffusion method to determined antimicrobial susceptibility pattern. The data were shifted from excel sheet to SPPS 21 IBMS version. Results The mean age (standard deviation) of patients was 51.60+26.59 years (Median age 58.50 years). Of the total, 64 were female and the remaining were male patients. It was found that most common pathogens in urine sample was E. coli. Maximum pathogens were sensitive to intra venous meropenem (65%), and fosfomycin (55%). Conclusion It is concluded that resistance patterns of uropathogens changes which results in treatment failure. Further, based on clinical practice, meropenem, fosfomycin, and cefepime had high sensitivity profile against catheter related infection in ICU.